PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI DAN KAPABILITAS SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN UMKM KOTA PALEMBANG - Yani, Resti; Putri, Andini Utari; Sari, Rafika (LP2M Universitas Bina Bangsa, 2025)
The data source in this research is primary data obtained from distributing questionnaires, with a population of 80,903 MSMEs in Palembang City in 2022. A sample of 100 MSMEs was obtained that implemented an accounting information system using the Slovin formula calculation. The sampling technique uses a non-probability method with purposive sampling technique. The analysis technique uses multiple linear regression. The research results were obtained partially. The application of the Accounting Information System (X1) has a positive and significant effect on the quality of financial reports (Y). Human Resource Capability (X2) has a positive and significant effect on the Quality of Financial Reports (Y). The implementation of the Accounting Information System (X1) and Human Resource Capabilities (X2) have a positive and significant effect simultaneously or together on the Quality of Financial Reports (Y).